1999
DOI: 10.1021/jf9902191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Invertase Activities and Reducing Sugar Content in Sweetpotato Stored at Different Temperatures

Abstract: Cured sweetpotato roots were stored at different temperatures (4.5, 15.6, and 24 degrees C) for 7 weeks and assayed for invertase activities and reducing sugar levels during two separate years. Invertase activities and reducing sugar concentration significantly increased in the roots kept at low temperature. Of the three types of invertases assayed, acid invertase specific activity was the highest. Acid invertase was the most influential in determining reducing sugar levels in stored sweetpotato. Cultivar diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
(25 reference statements)
2
13
0
4
Order By: Relevance
“…In these transgenic plants, the contents of glucose and fructose in the storage roots were remarkably reduced, while that of sucrose remained largely unchanged. This result is consistent with the previous reports describing a positive correlation between acid invertase activity and hexose content in sweetpotato storage roots (Takahata et al 1996;Huang et al 1999) and also suggests that Ibbfruct2 plays important roles in determining the utilization of sugar in the storage roots. Previous studies have reported that the expression of Ibbfruct2 was observed both in young and mature storage roots, while the expression of the other two genes (Ibbfruct1 and Ibbfruct3) was weak or undetectable in those tissues (Li and Zhang 2003;Wang et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…In these transgenic plants, the contents of glucose and fructose in the storage roots were remarkably reduced, while that of sucrose remained largely unchanged. This result is consistent with the previous reports describing a positive correlation between acid invertase activity and hexose content in sweetpotato storage roots (Takahata et al 1996;Huang et al 1999) and also suggests that Ibbfruct2 plays important roles in determining the utilization of sugar in the storage roots. Previous studies have reported that the expression of Ibbfruct2 was observed both in young and mature storage roots, while the expression of the other two genes (Ibbfruct1 and Ibbfruct3) was weak or undetectable in those tissues (Li and Zhang 2003;Wang et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The enzyme invertase, also called sucrase, catalyzes the hydrolysis of sucrose to glucose and fructose (Huang et al 1999; Zhang et al 2016). Invertase is found in the potential urine contaminant yeast (Fisher et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have examined the effects of different storage temperatures on sugar content in other plant products (Ding et al, 1998;Huang et al, 1999). During storage at cold temperatures, potato tubers accumulate free reducing sugars derived from the breakdown of starch to sucrose, which is then converted into glucose and fructose (Blenkinsop et al, 2004;McKenzie et al, 2013;Samotus et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The invertase transcript did not accumulate in potato tubers stored at 10°C, but in tubers stored at 1°C, the invertase transcript level increased markedly within 7 days (Zhou et al, 1999). Invertase activities and reducing sugar concentration also significantly increased in roots of sweet potato kept at a low temperature (Huang et al, 1999). Sucrose loss was shown not to be increased by cold storage in loquat fruit (Ding et al, 1998), while sucrose content was largely unaffected during cold storage in apple (Ackermann et al, 1992).…”
mentioning
confidence: 88%